Hospital Ownership and Financial Performance: What Explains the Different Findings in the Empirical Literature? - Yu-Chu Shen; Karen Eggleston; Joseph Lau; Christopher H. Schmid (SAGE Publishing, 2007)
This study applies meta-analytic methods to conduct a quantitative review of the empirical literature on hospital ownership since 1990. We examine four financial outcomes across 40 studies: cost, revenue, profit margin, and efficiency. We find that variation in the magnitudes of ownership effects can be explained by a study's research focus and methodology. Studies using empirical methods that control for few confounding factors tend to find larger differences between for-profit and not-for-profit hospitals than studies that control for a wider range of confounding factors. Functional form and sample size also matter. Failure to apply log transformation to highly skewed expenditure data yields misleadingly large estimated differences between for-profits and not-for-profits. Studies with fewer than 200 observations also produce larger point estimates and wide confidence intervals.